Formulação hierárquica do Método dos Elementos Finitos: refinamento auto-adaptativo versão P aplicado a problemas de elasticidade - Ribeiro, Fernando Luiz Bastos (1986)
This work is concerned with the development of a p version self-adaptive scheme of the Finite Element Method for a-posteriori error analysis and automatic refinement, in the resolution of linear static elasticity problems. Utilizing the hierarchical formulation of the method, the selective polynomial refinement is performed by means of iterative procedures, according to an error indicator distribution. As for the application of such methodology, analyses of plane elasticity, plate bending and shell problems are presented. The obtained results are compared with analytical solutions.